2016
DOI: 10.1128/aem.00495-16
|View full text |Cite
|
Sign up to set email alerts
|

Host-Specific Patterns of Genetic Diversity among IncI1-Iγ and IncK Plasmids Encoding CMY-2 β-Lactamase in Escherichia coli Isolates from Humans, Poultry Meat, Poultry, and Dogs in Denmark

Abstract: CMY-2 is the most common plasmid-mediated AmpC ␤-lactamase in Escherichia coli isolates of human and animal origin. The aim of this study was to elucidate the epidemiology of CMY-2-producing E. coli in Denmark. Strain and plasmid relatedness was studied in 93 CMY-2-producing clinical and commensal E. coli isolates collected from 2006 to 2012 from humans, retail poultry meat, broilers, and dogs. Multilocus sequence typing (MLST), antimicrobial susceptibility testing, and conjugation were performed in conjunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 40 publications
8
79
1
Order By: Relevance
“…In animals, the majority of identified AmpC enzymes have been of the CMY type (Table 2) (25, 56). A recent study performed in Denmark identified CMY-2-producing E. coli isolates from poultry meat, poultry, and dogs (57). The study showed that the dissemination of bla CMY-2 was mainly due to the spread of IncI1-γ and IncK plasmids.…”
Section: Acquired Ampc Cephalosporinasesmentioning
confidence: 92%
“…In animals, the majority of identified AmpC enzymes have been of the CMY type (Table 2) (25, 56). A recent study performed in Denmark identified CMY-2-producing E. coli isolates from poultry meat, poultry, and dogs (57). The study showed that the dissemination of bla CMY-2 was mainly due to the spread of IncI1-γ and IncK plasmids.…”
Section: Acquired Ampc Cephalosporinasesmentioning
confidence: 92%
“…CMY-2 is the most prevalent AmpC β-lactamase and has been globally disseminated among Enterobacteriaceae in humans, companion animals, food-producing animals, and retail meat (Bogaerts et al, 2015; Carmo et al, 2014; Hansen et al, 2016; Jacoby, 2009; Ma et al, 2012; Smet et al, 2010; Vogt et al, 2014; Wu et al, 2015). As shown in Table 2, AmpC β-lactamases have been reported in E. coli , K. pneumoniae , and Enterobacter cloacae isolates of wildlife origin in Europe, North America, and Asia, and particularly in central Europe, similar to ESBL-producing Enterobacteriaceae (Table 2).…”
Section: Plasmid-mediated Ampc β-Lactamase-producing Enterobacteriacementioning
confidence: 99%
“…Other studies investigating pAmpC-producing E. coli have detected the nearly identical kind of plasmid in healthy humans (Baudry et al, 2009; Porres-Osante et al, 2015; Hansen et al, 2016), poultry (Dierikx et al, 2010; Hansen et al, 2016; Mo et al, 2016), poultry meat (Egervärn et al, 2014), and dogs (Hansen et al, 2016). This prompted us to perform an in-depth analysis of bla CMY -2/4 -carrying IncB/O/K plasmids from E. coli isolated in three settings in Switzerland to determine their genetic relatedness, revealing a novel IncK-group variant, the IncK2.…”
Section: Introductionmentioning
confidence: 99%